ESTIMASI BEBAN PENCEMARAN POINT SOURCE DAN LIMBAH DOMESTIK DI SUNGAI KALIBARU TIMUR PROVINSI DKI JAKARTA, INDONESIA - Rahmat Pangestu; Etty Riani; Hefni Effendi (Graduate School Bogor Agricultural University (SPs IPB), 2017)
East Kalibaru River is one of the thirteen rivers flowing through Jakarta. East Kalibaru River has an important role in development of the region. Considering the increasing activities of people, settlements and number of industries along the East Kalibaru River, it is necessary to calculate contaminants load that discharged into the water body East Kalibaru. This study conducted to determine the point source and domestic waste pollution loads, using parameters of BOD, COD and TSS. The analysis showed that the total pollution loads such are calculated as 43.714 kg/day for BOD, 60.107 kg/day for COD and total 41.529 kg/day for TSS. Total pollution load discharged into river from point source effluent is amounted of 249 kg/day for BOD, 1.505 kg/day for COD and total 411 kg/day for TSS. Effect of domestic waste is very insignificant compared to the effect of point source that went into the river. The result suggest that approach that need to be done to reduce the burden of domestic waste water pollutants is by performing additional production or communal Wastewater Treatment Plant (WWTP) in densely populated areas.